2008
DOI: 10.5713/ajas.2008.80159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sucrose and Glycerol during the Freezing Step of Cryopreservation on the Viability of Goat Spermatozoa

Abstract: Four experiments were conducted to study the following: i) the influence of different concentrations of sucrose (0.15, 0.3 and 0.5 M with osmolality of 308, 500 and 760 mOsm/kg, respectively) in diluents and control diluent (370 mOsm/kg) on intensity of motility and progressive motility of goat sperm without rehydration and freezing step in four incubation periods (0, 0.5, 2 and 4 h after dilution); ii) the influence of gradual dilution (in 3 steps) on improvements in ascertained results of the first experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The use of sunflower lecithin has not been reported upon. The present study indicated decline in the percentage motility and other sperm quality parameters and agreed with previous studies on semen cryopreservation with varying semen extenders with (Salmani et al, 2014;Chelucci et al, 2014;Yotov, 2015) or without lecithin from plant origin (Ahmad et al, 2013;Farshad and Akhondzadeh, 2008;Gojen Singh et al, 2016). Studies have proven the valuable effects of soybean lecithin for cryopreservation of sperm in bull (Aires et al, 2003;Gonzales et al, 2003), ram (Forouzanfar et al, 2010;de Paz, et al, 2010) and goat (Roof et al, 2012;Salmani et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…The use of sunflower lecithin has not been reported upon. The present study indicated decline in the percentage motility and other sperm quality parameters and agreed with previous studies on semen cryopreservation with varying semen extenders with (Salmani et al, 2014;Chelucci et al, 2014;Yotov, 2015) or without lecithin from plant origin (Ahmad et al, 2013;Farshad and Akhondzadeh, 2008;Gojen Singh et al, 2016). Studies have proven the valuable effects of soybean lecithin for cryopreservation of sperm in bull (Aires et al, 2003;Gonzales et al, 2003), ram (Forouzanfar et al, 2010;de Paz, et al, 2010) and goat (Roof et al, 2012;Salmani et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Differences in abnormality values between T2 and T3 were not significant, but the lowest abnormality values for sperm were after T2 treatment (6.6800±1.702%). A good diluent provides differential osmotic pressure cryoprotection as well as protection from cold shock [29]. Lecithin from egg yolk can protect against cold shock and provide extracellular cryoprotection.…”
Section: Resultsmentioning
confidence: 99%
“…The choice to assess sucrose as an NP-CPA for our native trout was motivated by its beneficial effects obtained in mammal semen freezing and the fact that very little is known about sucrose in trout semen cryopreservation. In this regard, in mammals, several authors have reported sucrose as an NP-CPA agent in semen cryopreservation extenders [17,18,35,36,37,38,39,40], whilst in trout, the effects of sucrose as external cryoprotectant on the in vitro post-thaw quality have been studied in only two reports [21,22]. In fact, numerous studies have advised that sucrose can be utilized as a source of energy, as alternative sugar to glucose in the preparation of carbohydrate-based extenders, rather than being supplemented as a non-permeating agent [41,42,43,44,45].…”
Section: Discussionmentioning
confidence: 99%